Identity, Citizenship, and Political Conflict in Africa - Keller, Edmond J. (Edmond Joseph), 1942- (Indiana University Press, 2014)
Reflecting on the processes of nation-building and citizenship formation in Africa, Edmond J. Keller believes that although some deep parochial identities have eroded, they have not disappeared and may be more assertive than previously thought, especially in instances of political conflict. Keller reconsiders how national identity has been understood in Africa and presents new approaches to identity politics, intergroup relations, state-society relations, and notions of national citizenship and citizenship rights. Focusing on Nigeria, Ethiopia, Cote d'Ivoire, Kenya, and Rwanda, he lays the.